Pronunciation in EMI: Conceptualization, interlocutor anxiety and attitudes towards lecturer speech. - Gómez-Lacabex, Esther; Roothooft, Hanne (Journal of Multilingual Theories & Practices, 2023)
The consolidation of English as a global language has brought with it the need to reconceptualise aspects such as English pronunciation, which seems to be experiencing a detachment from the native norm and the integration of multicultural identities. EMI students have been reported to favour intelligibility over accurate pronunciation, as they represent a community of learners for whom English is a tool rather than a target. As previous research has reported that pronunciation may be an anxiety factor for students in speaking exchanges, this study explored how 126 EMI students envision the learning of pronunciation, their attitudes towards EMI teachers' pronunciation and their pronunciation anxiety upon interaction with different interlocutors in their EMI context: teachers, local peers, L1 English international peers and L2 English international peers. The data from a questionnaire and focus groups revealed that these EMI learners conceptualize pronunciation as a communication tool rather than a subject to be learnt; they revealed that they do not experience uneasiness during lessons owing to their lecturers' pronunciation, expressing that fluency is more important than pronunciation accuracy. Finally, they showed more pronunciation anxiety if the interlocutor was the teacher or an L1 English speaker than if it was a local peer or L2 English speaker.